CLIMATE CHANGE IN KYIV: WAYS TO CONTERACT AND MINIMIZE NEGATIVE EFFECTS - V. Bazylevych; G. Kupalova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2013)
ital issues of climate change in Kyiv are studied with elucidation of the need for developing a comprehensive research technique to analyse and assess a cumulative impact of the process. The study exposes anthropogenic and natural factors responsible for climate formation in Kyiv and the climatic changes. With an account for recent international experience the proposals are formulated how to make use of contemporary administrative, economic, legal and regulatory levers to forestall climatic changes in the capital and cope with the negative environmental aftermath.